Role of regulatory T cells and T helper 17 cells in the pathogenesis of hypertension: a review - Muliawan, Hary Sakti; Dwi Putra, Swastya; Amin, Hilman Zulkifli; Widyantoro, Bambang (Faculty of Medicine Universitas Indonesia, 2024)
The discovery of autoantibodies in artery samples from cadavers with hypertension over 50 years ago suggested a potential link between the immune system and hypertension. Since then, research exploring the role of the immune system in hypertension has emerged. Animal studies have demonstrated a strong correlation between regulatory T cells (Tregs) and T helper 17 (Th17) cells in hypertension development, yet studies on human hypertension remain limited. Tregs produce inhibitory cytokines such as interleukin (IL)-10 and transforming growth factor-β to act as anti-inflammatory cells that protect against hypertension. In contrast, Th17 cells, by producing IL-17A, function as pro-inflammatory cells that promote hypertension. Recently, a subset of cells known as IL-17A+FOXP3+Treg cells have been identified, which can produce IL-17 and act as inflammatory cells under certain conditions. Understanding the basic mechanisms by which the immune system influences hypertension could lead to targeted immunotherapies for hypertension in the future. Thus, we highlighted the role of Tregs and Th17 cells in the development of hypertension and their potential as targets for therapy. Our findings confirmed the role of Tregs and Th17 cells in the pathogenesis of hypertension.